2019
DOI: 10.1088/1361-665x/ab143c
|View full text |Cite
|
Sign up to set email alerts
|

Fluidic origami cellular structure with asymmetric quasi-zero stiffness for low-frequency vibration isolation

Abstract: This study investigates a unique asymmetric quasi-zero stiffness (QZS) property from the pressurized fluidic origami cellular structure, and examines the feasibility and efficiency of using this nonlinear property for low-frequency vibration isolation. This QZS property of fluidic origami stems from the nonlinear geometric relationships between folding and internal volume change, and it can be programmed by tailoring the constituent Miura-Ori crease design. Different fluidic origami cellular structure designs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…In the future, the application of the proposed ZBSO metamaterial in other fields will be further explored, e.g. low-frequency vibration isolation load-bearing structures [43].…”
Section: Varying the Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, the application of the proposed ZBSO metamaterial in other fields will be further explored, e.g. low-frequency vibration isolation load-bearing structures [43].…”
Section: Varying the Microstructuresmentioning
confidence: 99%
“…stacking order and sacking way [42]. For instance, the high-static-low-dynamic stiffness property can be harnessed by SOMM, which is extremely important in the field of low-frequency vibration isolation [43][44][45][46]. Our previous work revealed that stacking two Miura sheets to form a SOMM can achieve the realization of tailoring the dynamic stiffness [47].…”
Section: Introductionmentioning
confidence: 99%
“…Other negative stiffness elements, such as bio-inspired structures [18] , [19] and electromagnetic structures [20] , [21] , [22] , were investigated for generating QZS feature. Recently, metamaterials and origami structures were also applied to achieve the QZS characteristics [23] , [24] , [25] , [26] , [27] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a column with a pre-folded pattern could be used for suspension components of a building or bridge, which enables avoiding damage caused by vibrational energy excitation coming from earthquakes or wind (Ishida et al, 2017;Nikoo et al, 2020). In biomechanics application, the pre-folded thin-walled column could be used for biomedical stents (Kuribayashi et al, 2006) and suspension for prosthetic devices (Sadeghi & Li, 2019). Furthermore, the column is also suitable for suspension components in robotic structures, which usually have complex structures and irregular shapes (Castiblanco et al, 2021;Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%